Health-Promoting Properties of Lactobacilli in Fermented Dairy Products - Widyastuti, Yantyati; Febrisiantosa, Andi; Tidona, Flavio (Frontiers in Microbiology, 2021)
Bacteria of the genus Lactobacillus have been employed in food fermentation for decades. Fermented dairy products, such as cheese and yogurt, are products of high value known as functional food and widely consumed due to their positive health impact. Fermentation was originally based on conversion of carbohydrate into organic acids, mostly lactic acid, intended to preserve nutrient in milk, but then it develops in other disclosure of capabilities associates with health benefit. It is expected that during the manufacture of fermented dairy products, some bioactive peptides from milk protein are released through proteolysis. Lactobacilli have been recognized and received increasing attention as probiotics by balancing gut microbial population. Information of molecular mechanisms of genome sequence focusing on the microbial that normally inhabit gut may explain as to how these bacteria positively give impact on improving host health. Recent postbiotics concept revealed that health benefit can also be associated after bacterial lysis. This mini review focuses on the contribution of lactobacilli in dairy fermentation with health-promoting properties on human health.